Building capacity of small-medium cities’ local authorities to implement MaaS and other innovative transport schemes - Founta, A.; Papadopoulou, O.; Kalakou, S.; Georgiadis, G. (Advances in Mobility-as-a-Service Systems. Advances in Intelligent Systems and Computing, 2020)
Sustainable development requirements in combination with extreme technological evolution have changed the way mobility is considered, creating challenges to Local Authorities (L?s) both in planning and implementation phases of mobility solutions. This paper focuses on the capacity building of LAs to deliver Mobility-as-a-Service (MaaS) and other innovative transport schemes as part of Sustainable Urban Mobility Plans (SUMPs). It presents a methodological approach for the design and employment of an integrated learning tool that intends to increase the adoption rates of measures’ packages through LAs knowledge strengthening. The learning tool consists of a detailed facilitator guide to run an one-day classroom course along with the conceptual background and necessary training material. The methodological approach consists of a multilevel and multicriteria process that integrates the results/outcomes of the assessment of the cities capacity to implement SUMP through an evaluation framework. The classroom course has been structured in order to clarify the value of MaaS and other innovative measures for small-medium cities, analyze successful case studies under the spectrum of overcoming challenges efficiently, present tools and guidelines supporting collaboration between team members. The results of this work have been validated through the pilot application to six LAs. The overall evaluation of the pilots showed that content’s accuracy and achievement of workshop’s objectives was more than satisfactory (more than 50% of the participants gave the highest rate) and participants became more engaged with SUMP measures implementation.